Pengaruh Media Gambar Terhadap Hasil Belajar Bahasa Indonesia Pada Pembelajaran Puisi Pada Siswa di Sekolah - Yuni Hartati; Sri Hastati; Nasaruddin Nasaruddin; Abrina Maulidnawati; Erniati Erniati (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
This study aims (1) to find out the description of the use of image media in poetry learning in class IX E UPTD SMPN 14 Tanralili, (2) to determine the results of learning Indonesian in poetry learning in class IX E UPTD SMPN 14 Tanralili (3) To determine knowing the effect of picture media in improving Indonesian language learning outcomes in poetry learning for class IX E UPTD SMPN 14 Tanralili students. The data collection techniques of this research are (1) tests which include pretest, treatment, and posttest, and (2) documentation. The data analysis technique in this study used the t-test. The results of this study indicate that the pretest was categorized as very low, obtained 9 students who completed poetry learning by 29.03% who got a score of 70 and above (meets KKM) and 22 students who did not complete 70.97% who got value of 70 and below (does not meet the KKM). Meanwhile, after giving or using the image media, the results of the final test (posttest) in the high category were obtained, 28 students who completed poetry learning were 90.32% who scored 70 and above and 3 students who had not completed 9.68% got value 70 and below.